# math

posted by .

simplify

(2x)^3 + 2^3 x

a) 8x^3
b) 16x^3
c)8(x^3+x)
d) 4(x^3+x)

• math -

This was correctly answered after you first posted it.
Did you not check your post ?

## Similar Questions

1. ### Intermediate Algebra

Am I going in the right track? 8x -1/x + 5x - 3/2x = 16x^2 - 2x/2x^2 + 5x^2 - 3x/2x^2 16x^2 - 2x + 5x^2 - 3x/2x^2 =21x^2 - 5/2x^2 Find the LCD 6/7z- 28, 8/x^2 -4x = 7x(x-4) Simplify 3x^2 - 2x/15x-10 = x/5 Let's start by looking at
2. ### algebra

Solve the system by addition or substitution. 16x-4y=20 y=4x-4 I ask for help with this and forgot to add the problem. can anyone help me understand how to do this?
3. ### Algebra

There are two solutions to | 16x - 5 | = 3. The greatest solution is ___. Since the expression, 16x - 5, can be either positive or negative, solve for both. 16x - 5 = 3 16x = 8 x = .5 -(16x - 5) = 3 -16x + 5 = 3 -16x = -2 x = 1/8 You …
4. ### math-algebra

Simplify: [(4x^3y)(4^2xy)^-1]/(4xy^2) A. x /16y^2 B. 16x/y^2 C. x^2/16y D. y/16x^2
5. ### Math

find any stationary points of the function g(x) = (2x-3)square root of 5+16x-4x^2 (0 less than or equal to x less than or equal to 4) and use the first derivative test to classify each stationary point as a local maximum or local minimum …
6. ### Math

5(-3x - 2) - (x - 3) = -4(4x + 5) + 13 Answer Multiply factors. -15x - 10 - x + 3 = -16x - 20 +13 Group like terms. -16x - 7 = -16x - 7 Add 16x + 7 to both sides and write the equation as follows 0 = 0
7. ### math

The question is (2x+1)^2-2(2x^2-1) in simplest form Is this correct?
8. ### math

Please check my answers! Simplify the product. 7x(x+4) A. 7x^2+4 B. 7x^2+28x <<<< C. 8x+4 D. 8x+11 Simplify the product. 4x (2x^3 - 7x^2 + x) A. 8x^4-28^3+4x^2 <<<<< B. 16x^4-7x^2+4x C. 8x^4-7x^2+x D. 16x^4-3x^3+4x^2 …
9. ### Math

I sent this in a little while back but the file got corrupted and I have to re do it and I forgot the answer please if it is not done today I fail the year. Simplify the polynomial 16x^2 + 2 + 2x - 15x^2 - 1 + 14x A:31x^2 + 16x + 1*** …
10. ### Math

1. 16x^2 + 2 + 2x - 15x^2 - 1 + 14x a. 31x^2 + 16x + 1 b. x^2 - 12x + 1 c. x^2 + 16x + 1* d. x^2 + 16x + 2 2. 3x^2 + 6 - 2x + 5x - 4^2 + 9 a. -x^2 + 3x + 15* b. 7x^2 + 3x + 3 c. x^2 - 3x + 15 d. -x^2 + 7x + 15 3. 2x^2 + 6x - 7x + 8 …

More Similar Questions

Post a New Question